2020
DOI: 10.1186/s13287-020-01618-6
|View full text |Cite
|
Sign up to set email alerts
|

Selection of human induced pluripotent stem cells lines optimization of cardiomyocytes differentiation in an integrated suspension microcarrier bioreactor

Abstract: Background: The production of large quantities of cardiomyocyte is essential for the needs of cellular therapies. This study describes the selection of a human-induced pluripotent cell (hiPSC) line suitable for production of cardiomyocytes in a fully integrated bioprocess of stem cell expansion and differentiation in microcarrier stirred tank reactor. Methods: Five hiPSC lines were evaluated first for their cardiac differentiation efficiency in monolayer cultures followed by their expansion and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The GiWi method is among the most efficient strategies for differentiating hiPSCs into cardiomyocytes; however, it may not be sufficiently scalable to produce the billions of hiPSC-CMs needed for treatment of myocardial disease or for highthroughput drug-testing, because it is typically conducted with 2D cell sheets in 6-well culture plates (Sharma et al, 2015). hiPSC-CMs can also be produced in suspension culture (Shafa et al, 2011;Kempf et al, 2014Kempf et al, , 2015Kempf et al, , 2016Fonoudi et al, 2016;Halloin et al, 2019;Hamad et al, 2019;Chang et al, 2020;Laco et al, 2020;Miwa et al, 2020), which is more compatible with largescale production, and the GiWi-based suspension-differentiation protocol introduced here incorporates a number of other key innovations, such as (1) the use of hiPSC culture media that was designed specifically for 3D culture and supplied via a fed batch reactor, (2) a filtration step before differentiation to reduce the heterogeneity of the spheroid population, (3) partial media changes on day 3 and from day 12 onward, which reduced processing time, and (4) direct incorporation of metabolic purification, which increased the purity of the differentiated hiPSC-CM populations to > 98%. Furthermore, whereas newly differentiated hiPSC-CMs are more phenotypically similar to fetal than to adult cardiomyocytes (Xu et al, 2009;Gupta et al, 2010;Yang et al, 2014;van den Berg et al, 2015), our results suggest that at least some markers for cardiomyocyte maturation tended to be more highly expressed in suspension-differentiated than monolayer-differentiated hiPSC-CMs; this observation is consistent with previous reports that 3D culture conditions appear to promote hiPSC-CM maturity (Correia et al, 2018;Beauchamp et al, 2020;Giacomelli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GiWi method is among the most efficient strategies for differentiating hiPSCs into cardiomyocytes; however, it may not be sufficiently scalable to produce the billions of hiPSC-CMs needed for treatment of myocardial disease or for highthroughput drug-testing, because it is typically conducted with 2D cell sheets in 6-well culture plates (Sharma et al, 2015). hiPSC-CMs can also be produced in suspension culture (Shafa et al, 2011;Kempf et al, 2014Kempf et al, , 2015Kempf et al, , 2016Fonoudi et al, 2016;Halloin et al, 2019;Hamad et al, 2019;Chang et al, 2020;Laco et al, 2020;Miwa et al, 2020), which is more compatible with largescale production, and the GiWi-based suspension-differentiation protocol introduced here incorporates a number of other key innovations, such as (1) the use of hiPSC culture media that was designed specifically for 3D culture and supplied via a fed batch reactor, (2) a filtration step before differentiation to reduce the heterogeneity of the spheroid population, (3) partial media changes on day 3 and from day 12 onward, which reduced processing time, and (4) direct incorporation of metabolic purification, which increased the purity of the differentiated hiPSC-CM populations to > 98%. Furthermore, whereas newly differentiated hiPSC-CMs are more phenotypically similar to fetal than to adult cardiomyocytes (Xu et al, 2009;Gupta et al, 2010;Yang et al, 2014;van den Berg et al, 2015), our results suggest that at least some markers for cardiomyocyte maturation tended to be more highly expressed in suspension-differentiated than monolayer-differentiated hiPSC-CMs; this observation is consistent with previous reports that 3D culture conditions appear to promote hiPSC-CM maturity (Correia et al, 2018;Beauchamp et al, 2020;Giacomelli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, because the GiWi method is typically used to differentiate two-dimensional (2D) cell sheets in 6-well culture plates (Sharma et al, 2015), it may not be sufficiently scalable to produce the number of hiPSC-CMs needed for high-throughput cardiotoxicity assessments or for clinical applications such as the treatment of acute myocardial infarction (MI), which often results in the loss of ∼1 billion cardiomyocytes (Chong et al, 2014;Kropp et al, 2016;Dunn and Palecek, 2018). Higher yields may be achievable with multilayered/stacked flasks or multicarrier-based systems, but neither of these methods have been fully scaled, and both require materials and reagents that are not readily available (Ting et al, 2014(Ting et al, , 2018Breckwoldt et al, 2017;Le and Hasegawa, 2019;Chang et al, 2020;Laco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, we explored the possibility of using ZM, an inhibitor of Aur-A (which controls the cell cycle), in the differentiation stage. The differentiation of CMs is related to the cell cycle, and the Wnt/Gsk3β mechanism in CMs varies depending on the confluence of hiPSCs at the beginning of differentiation [ 18 , 42 ]. Our experimental results confirmed that the cell cycle ratio changed according to the confluence of hiPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The culture in the suspension of cells that are adhesion-dependent for survival and proliferation can be obtained through the use of supporting matrices known as microcarriers [ 81 ]. Laco et al (2020) developed a microcarrier culture system in a tank bioreactor that allowed scalable iPSC expansion and CM differentiation and purification, reaching a yield of ~40 CMs per iPSC seeded after 22 days in culture [ 82 ]. A future intension of bioreactor use will be the production of large amounts of high quality CMs in GMP manufacturing, to improve their use in clinical practice.…”
Section: Differentiation Of Cardiac Cells From Ipscsmentioning
confidence: 99%